2016
DOI: 10.1002/1873-3468.12196
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel bile acids as biomarkers for the early diagnosis of Niemann‐Pick C disease

Abstract: This article describes a rapid UPLC‐MS/MS method to quantitate novel bile acids in biological fluids and the evaluation of their diagnostic potential in Niemann‐Pick C (NPC). Two new compounds, NPCBA1 (3β‐hydroxy,7β‐N‐acetylglucosaminyl‐5‐cholenoic acid) and NPCBA2 (probably 3β,5α,6β‐trihydroxycholanoyl‐glycine), were observed to accumulate preferentially in NPC patients: median plasma concentrations of NPCBA1 and NPCBA2 were 40‐ and 10‐fold higher in patients than in controls. However, NPCBA1 concentrations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 87 publications
(112 citation statements)
references
References 32 publications
3
108
0
1
Order By: Relevance
“…Sulfate or glycine conjugation of general drug metabolism appears to be very ef cient at birth 27,28 , while the maturation of sulfation to UDCA was not likely to be earlier than N-acethylglucosaminidation. The UGT3A1 de ciency is reported to be about 10% in the study of the Niemann Pick Type C biomarker analyzing 3 -sulfooxy-7 -N-acethylglucosaminyl-5 -cholen-24-oic acid 29 , and similarly in this study, 2 of 21 samples showed no UDCAs-7NAG.…”
Section: Discussionsupporting
confidence: 81%
“…Sulfate or glycine conjugation of general drug metabolism appears to be very ef cient at birth 27,28 , while the maturation of sulfation to UDCA was not likely to be earlier than N-acethylglucosaminidation. The UGT3A1 de ciency is reported to be about 10% in the study of the Niemann Pick Type C biomarker analyzing 3 -sulfooxy-7 -N-acethylglucosaminyl-5 -cholen-24-oic acid 29 , and similarly in this study, 2 of 21 samples showed no UDCAs-7NAG.…”
Section: Discussionsupporting
confidence: 81%
“…Analysis of cholanoic acids (normal bile acids) and their taurine and glycine conjugates was performed by targeted UPLC-MS/MS essentially as described previously (23), with modifications to include the analysis of the cholestanoic acids (C27 bile acids) THCA and [27,27,27-D 3 ]-THCA, purchased from Herman Ten Brink of the VU Medical Centre, Amsterdam, The Netherlands. UPLC retention times and mass spectrometry transitions for the C27 bile acids are shown in Table S3.…”
Section: Methodsmentioning
confidence: 99%
“…3β-Sulfooxy-7β-hydroxy-5-cholen-24-oic acid is the precursor of SNAG-Δ 5 -CA. UDP glycosyltransferase (UGT) 3A1 catalyzes the transfer of Nacetylglucosamine from UDP N-acetylglucosamine to the 7β-hydroxy group on ursodeoxycholic acid, [17][18][19] and Mazzacuva et al 20) reported that the same enzyme catalyzes the transfer of N-acetylglucosamine onto 3β,7β-dihydroxy-5-cholenoic acid. Moreover, the same authors showed that the inactivation of UGT3A1 by genetic mutation suppress the production of 3β-hydroxy-7β-N-acetylglucosaminyl-5-cholenoic acid in NPC patients.…”
Section: Resultsmentioning
confidence: 99%